A Novel Fibrinolysis Resistance Capacity Assay Can Detect Fibrinolytic Phenotypes in Trauma Patients - Barrett, Christopher D.; Suzuki, Yuko; Moore, Ernest E.; Moore, Hunter B.; Maginot, Elizabeth R.; White, Collin M.; Siddiqui, Halima; Gawargi, Flobater I.; Chandler, James G.; Sauaia, Angela; Urano, Tetsumei (Thrombosis and Haemostasis, 2025)
Background To evaluate residual fibrinolysis resistance activity (FRA) in plasma, a detergent-modified plasma clot lysis assay time (dPCLT) was established in which α2-antiplasmin (A2AP) and plasminogen activator inhibitor type 1 (PAI-1) are inactivated without impacting protease activity. We applied this novel assay to severely injured trauma patients’ plasma.Material and Methods Tissue-type plasminogen activator (tPA)-induced plasma clot lysis assays were conducted after detergents- (dPCLT) or vehicle- (sPCLT) treatment, and time to 50% clot lysis was measured (“transition midpoint”, T m). Residual FRA was then calculated as ([sPCLT T m] - [dPCLT T m]/[sPCLT T m]) x100% = Δ Tm PCLT (%). Assay results were compared to rapid thromboelastography (TEG) LY30, tPA TEG LY30, and plasma fibrinolysis biomarkers in polytrauma patients’ plasma (N=43).Results Δ Tm PCLT(%) in normal plasma (N=5) was 63.0 ± 8.3 whereas in A2AP-depleted plasma was -19.1 ± 1.3%, Plasmin-antiplasmin (PAP) complex increased after complete lysis of sPCLT, whereas that in dPCLT was negligible in normal plasma. In trauma plasma, significant correlations between Δ Tm PCLT and active PAI-1 (r = 0.85, p<0.0001), PAP complex (r = -0.85, p<0.0001), free A2AP (r = 0.66, p<0.0001), total A2AP levels (r = 0.52, p=0.001) and tPA TEG LY30 (r = -0.85, p<0.0001) were found. dPCLT in hyperfibrinolysis patients diagnosed by tPA TEG was significantly shorter than those with low fibrinolysis [10.2 ± 6.4 minutes versus 20.2 ± 2.1 minutes, p=0.0006].Conclusion Hyperfibrinolysis after trauma is significantly related to exhaustion of FRA, and our novel assay appears to quickly assess this state and may be a useful clinical diagnostic after additional validation.Key Points
Keywords: fibrinolysis inhibitors; fibrinolytic disorders; surgery; hypercoagulability